Creutzfeldt-Jakob disease: a survey of 14 patients Doença de Creutzfeldt-Jakob: relato de 14 pacientes - Paulo E. Marchiori; Noboru Yasuda; Helga C. A. Azevedo; Mônica Órfão; Dagoberto Callegaro; Fábio I. Yamamoto; Milberto Scaff (Arquivos de Neuro-Psiquiatria)
Creutzfeldt-Jakob disease (CJD) is a transmissible disease of the nervous system causatively related to the presence of an abnormal prion protein, with dementia, myoclonic jerks, and periodic EEG activity. Fourteen patients (7 females and 7 males) ranging from 26 to 76 years of age (median 59 years) were evaluated between 1974 and 1995 at the Neurologic Clinic of São Paulo University School of Medicine. The average duration of the disease was 12 months (3.5 - 34 months). Early clinical findings were: behaviour changes in 7 patients, dementia in 4, visual disturbances in 4, vertigo in 2, tremor in 9, and dystonia in one. Advanced symptoms were dementia and myoclonus in all patients. Pyramidal tract dysfunction was found in 6, cerebellar ataxia in 2, seizures in 3, nystagmus and vertigo in 4, and peripheral nervous system involvement in 2. Atypical clinical forms were found in 5 patients. Periodic EEG activity was found in 10 patients. Cerebrospinal fluid evaluation showed pleocytosis in 1 patient, higher protein content in 2, and higher gamma globulin level in 2. In 10 patients anatomopathological evidence in the central nervous system confirmed the clinical diagnosis by presenting with status spongiosus. All except one patient presented with the sporadic form of the disease. As encefalopatias espongiformes humanas ou doenças priônicas são um grupo de doenças rapidamente progressivas caracterizadas por déficit cognitivo, ataxia, mioclonia e manifestações visuais, piramidais e extrapiramidais. A doença de Creutzfeldt-Jakob (DCT) pode apresentar forma iatrogênica, genética e esporádica. Os autores apresentam 14 pacientes com DCJ forma esporádica e um com forma familial, acompanhados na Disciplina de Neurologia Clínica da FMUSP, no período de 1974 a 1995. Sete eram do sexo feminino e 7 do sexo masculino, com idade variando de 26 a 76 anos (média de 59 anos). As manifestações neurológicas iniciais foram distúrbio do comportamento em 7, demência em 4, deficiência visual em 4, vertigens em 2, tremor em 9 e distonia em um paciente. Posteriormente, demência e mioclonias ocorreram em todos os pacientes. Foram encontrados: disfunção do trato piramidal em 6, vertigens em 4, convulsões em 3, ataxia cerebelar em 2, distúrbio do sistema nervoso periférico em 2. A forma atípica da doença ocorreu em 5 pacientes. Atividade periódica ao eletroencefalograma ocorreu em 10 pacientes. O líquido cefalorraquidiano mostrou pleocitose em 1, hiperproteinorraquia em 2 e hipergamaglobulinorraquia em 2. O estudo anátomo-patológico do sistema nervoso central, feito em 10, revelou alterações vacuolares do neurópilo em todos os pacientes.